Los Gobiernos Autónomos Descentralizados Parroquiales Rurales frente al ejercicio de participación ciudadana: análisis de los GADS parroquiales rurales del cantón Chone - Rivero García, Elberth Cecilio (2022)
Citizen participation is a right established by the Constitution, and that must be exercised in the different instances of participation, the GADPs in Chone canton have promoted intervention through certain mandatory mechanisms trying to get the community involved in the efforts they execute; participation in decision-making in matters of public interest was evaluated in the study, which aimed to determine the level of citizen participation in the administration of rural GADPs in Chone canton in Manabí province. For the execution of the work, phases were applied with activities that denoted the compliance of the social actors. A comparative table was prepared that showed the link between the laws that govern citizen participation, an interview was also applied to each of the presidents of the GADPs in which several aspects related to the mechanisms used in each GADPs were determined, the application of the focus groups with the community leaders provided relevant data, which were quantified and subsequently tabulated, revealing the appreciation of the protagonists, which allowed establishing the level of participation, the Roger Hart Ladder was used, this led to proposing actions of improvements that motivate and generate a commitment to the citizens and the GADPs to promote public management based on efficiency, transparency and effectiveness. It should be noted that in the GADPs investigated, only three mechanisms have been developed, being a negative aspect for the protagonists, limiting the intervention of both social actors.